2007
DOI: 10.1037/0882-7974.22.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Social exchanges and subjective well-being among older Chinese: Does age make a difference?

Abstract: We examined the effects of social support and negative interactions on life satisfaction and depressed affect among older Chinese, and age differences in these associations. The sample consisted of 2,943 Chinese elders aged 60 to 94 years old. Structural equation modeling (SEM) results suggest that both social support and negative interactions have significant contributions to life satisfaction and depressed affect. Social support has stronger effects than negative interactions on life satisfaction; their effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 32 publications
6
49
2
Order By: Relevance
“…50 Cross-cultural stresses and a lack of social support may interact to increase pain. These two factors could interact to increase pain and depression, as social support represents an important buffer against stress 35, 46 ; hence, the combination of acculturation stress and low social support may be particularly potent. In addition, the impact of acculturation stress and low social support may be magnified among Asian Americans with comorbid pain and depression; both are risk factors for pain and depression, 34, 37, 45, 59 which can, in turn, be mutually exacerbating.…”
Section: Discussionmentioning
confidence: 99%
“…50 Cross-cultural stresses and a lack of social support may interact to increase pain. These two factors could interact to increase pain and depression, as social support represents an important buffer against stress 35, 46 ; hence, the combination of acculturation stress and low social support may be particularly potent. In addition, the impact of acculturation stress and low social support may be magnified among Asian Americans with comorbid pain and depression; both are risk factors for pain and depression, 34, 37, 45, 59 which can, in turn, be mutually exacerbating.…”
Section: Discussionmentioning
confidence: 99%
“…Change in marital status is related to changes in life satisfaction trajectory (Mroczek and Sprio 2005). In addition to marital status, the quality of social relationships is related to life satisfaction (Li and Liang 2007;Röcke and Lachman 2008), and the relationship is stronger in women than men, regardless of marital status (Cheng and Chang 2006). Social support manifests its buffer effect particularly for people who were experiencing bad times.…”
Section: Physical Mental and Social Dimensions Of Health And Life Smentioning
confidence: 96%
“…For younger individuals, only support received from their partner was associated with lower depressive symptoms, whereas for older persons support from all sources was predictive of lower depressive symptoms. Moreover, research with young-and old-aged individuals demonstrated that with increasing age positive associations between social support and well-being become stronger (e.g., Li and Liang 2007;Krause 2005). This again might be explained by differences in the sources of support across ages: receiving emotional social support from close social network partners, which is more likely for older adults due to the selective composition of the social network, might be more beneficial for one's well-being than received emotional social support from both close and distal social network partners, as it should be the case for younger adults.…”
Section: Age Differences Of Social Supportmentioning
confidence: 99%